Acesso venoso central percutâneo , via veia jugular externa, pelatécnica de Seldinger em crianças: é imprescindível a inserção do fio guia até a veia cava superior para o sucesso do cateterismo? - Paulo Custodio Furtado Cruzeiro (2010)
The central venous catheterization is a procedure often necessary toadminister medications, blood products and parenteral nutrition in hospitalized children. Traditionally it is accomplished by a puncture of the deep veins (subclavian, internal jugular or femoral) using the Seldinger technique or by venous dissection. Although essential in many clinical situations, may be associated with significant morbidity. The external jugular vein (EJV) is lower morbidity alternative for the performance of percutaneous central venous catheterization (PCVC) in children but it has low success rates according to medical literature, which makes it less used in the routine of pediatric surgeon. A modified technique for the realization of PCVC, via EJV, is proposed in order to increase the effectiveness of this procedure in children. In the modified technique proposed, after the puncture EJV, the guide wire that meets resistance on the path toward the superior vena cava (SVC) and is retained only in a peripheral position and used to insert the catheter into the vein. Subsequently, the catheter is advanced and can access the SVC regardless of the progression of the guide wire. The aim of this study was to describe this modified technique and evaluate its effectiveness during the PCVC Seldinger technique via EJV in children. This is a prospective study in 100 children (60 boys and 40 girls) aged between two days and 17 years (mean 5.6 ± 4.6 years) and weighing between 2.2 and 58 kg (mean 18 ± 12.5 kg) that underwent PCVC between May 2008 and June 2009. The PCVC Seldinger technique, with the introduction of the guide wire to the SVC (STAGE 1) was an initial choice in all cases, and provided a success rate of 13% but poor positioning of the catheter ocurred in two cases (15.6% ). In 87 children was performed PCVC, with the guide wire in a peripheral position (STAGE 2). At this stage, the success rate was 96.6% (84 cases), with poor positioning of the catheter in ten cases (13.7%). There was a statistically significant difference between the success rates of the two stages (p = 0.039). There was no statistically significant difference in the frequency for which the catheter was positioned incorrectly between stages. After the X-ray control, 85 catheters (87.6%) were positioned properly in the SVC. There were seven (7.2%) hematomas during catheterization of no clinical significance.The EJV is an excellent alternative to the completion of the PCVC Seldinger technique in children. The modified technique proposed significantly increased the success rate of the PCVC through this vein.The PCVC Seldinger technique via EJV, with the guide wire in a peripheral position is a safe and effective option for obtaining percutaneous central venous access in children. Therefore, the insertion of the guide wire to the SVC is not essential to completion of the PCVC successfully in this route